Panoramas contemporâneos dos Ambientes Virtuais de Aprendizagem: as transformações no ambiente de ensino e aprendizagem virtual e o surgimento do arquiteto educacional - Kanô, Angélica Lúcia (2014)
This master s thesis was developed to try to understand the transformations in the contemporary landscape of Virtual Learning Environments through comparative studies and specific readings. Some practical cases were brought in support of the theory, such as the development of the interface in light of the history of the creation and adaptation of Apple, in order to reach a new audience. The possible opening and closing of the LMS and design strategies found in Social Networking Success, following the development of the LSM s Blackboard Learn and its digital marketing Facebook Social Network. Converging the questions and assumptions found, there would be a professional with relevant skills to perform these new designs of Virtual Learning Environments in a contemporary overview of E-Learning? During the search process, the main theoretical frameworks were Manuel Castells, Pierre Lévy, Virgina Kastrup, G. Deleuze, F. Guattari, Elizabeth Adams, O'Reilly, J. Dron and T. Anderson. As a result, we sought to provide clues about the approach of the LMSs with the Social Networks, to try to understand the changes and bring a small (but significant) contribution to the contemporary panorama of E-Learning. Regarding the education agent to articulate and apply this new landscape imaginable to LMS, we propose the idea of a new professional, Educational Architect